Integrated Analyses of Transcriptome and Chlorophyll Fluorescence Characteristics Reveal the Mechanism Underlying Saline–Alkali Stress Tolerance in Kosteletzkya pentacarpos - Zhou, Jian; Qi, Anguo; Wang, Baoquan; Zhang, Xiaojing; Dong, Qidi; Liu, Jinxiu (Frontiers in Plant Science, 2022)
Abstract: In recent years, soil salinization has become increasingly severe, and the ecological functions of saline–alkali soils have deteriorated because of the lack of plants. Therefore, understanding the tolerance mechanisms of saline–alkali-tolerant plants has become crucial to restore the ecological functions of saline–alkali soils. In this study, we evaluated the molecular mechanism underlying the tolerance of Kosteletzkya pentacarpos L. (seashore mallow) seedlings treated with 0.05% or 0.5% saline–alkali solution (NaCl: NaHCO3 = 4:1 mass ratio) for 1 and 7 days. We identified the key genes involved in tolerance to saline–alkali stress using orthogonal partial least squares regression analysis (OPLS-RA) based on both chlorophyll fluorescence indexes and stress-responsive genes using transcriptome analysis, and, finally, validated their expression using qRT-PCR. We observed minor changes in the maximum photochemical efficiency of the stressed seedlings, whose photosynthetic performance remained stable. Moreover, compared to the control, other indicators varied more evidently on day 7 of 0.5% saline–alkali treatment, but no variations were observed in other treatments. Transcriptome analysis revealed a total of 54,601 full-length sequences, with predominantly downregulated differentially expressed gene (DEG) expression. In the high concentration treatment, the expression of 89.11% and 88.38% of DEGs was downregulated on days 1 and 7, respectively. Furthermore, nine key genes, including KpAGO4, KpLARP1C, and KpPUB33, were involved in negative regulatory pathways, such as siRNA-mediated DNA methylation, inhibition of 5′-terminal oligopyrimidine mRNA translation, ubiquitin/proteasome degradation, and other pathways, including programmed cell death. Finally, quantitative analysis suggested that the expression of key genes was essentially downregulated. Thus, these genes can be used in plant molecular breeding in the future to generate efficient saline–alkali–tolerant plant germplasm resources to improve the ecological functions of saline–alkali landscapes.